Harry Potter and the Goblet of Fire - Book 4 Book 4 - Rowling, J. K. (Joanne Kathleen); GrandPre, Mary (New York : Arthur A. Levine Books, 2000)
Fourteen-year-old Harry Potter joins the Weasleys at the Quidditch World Cup, then enters his fourth year at Hogwarts Academy where he is mysteriously entered in an unusual contest that challenges his wizarding skills, friendships and character, amid signs that an old enemy is growing stronger.
Sequel to: Harry Potter and the prisoner of Azkaban.
Keywords: Potter, Harry (Fictitious character) -- Juvenile fiction; Granger, Hermione (Fictitious character) -- Juvenile fiction; Weasley, Ron (Fictitiouis character) -- Juvenile fiction; Hogwarts School of Witchcraft and Wizardry (Imaginary place) -- Juvenile fiction; Wizards -- Juvenile fiction; Magic -- Juvenile fiction; Schools -- Juvenile fiction; England -- Juvenile fiction; Fantasy -- Juvenile fiction